Nerve conduction studies of the axillary, musculocutaneous and radial nerves in elite ice hockey players - Colak, T.; Bamaç, B.; Alemdar, M.; Maci, T.; Selekler, H.; Özbek, A.; Colak, S.; Dincer, Ö. (The Journal of Sports Medicine and Physical Fitness, 2009)
Aim. The peripheral nerves of the upper extremity are exposed to acute and chronic mechanical injuries in ice hockey players, because of the high repetition of motions, high muscular forces and extreme shoulder positions. This study was performed to evaluate the effect of ice hockey playing on the axillary, musculocutaneous and radial nerves crossing the upper arm region. Methods. The ice hockey group consisted of 20 first-division male ice hockey players and the control group consisted of 20 non-active males. The neurophysiological study consisted of motor nerve conduction latency of the axillary, musculocutaneous and radial nerves. Results. The values of distal motor latency (DML) of the axillary, radial and musculocutaneous nerves were significantly prolonged in the ice hockey players compared with the controls. Ice hockey can repetitively stress the upper extremity during shooting, because of forceful throwing to move the puck from the stick blade to the opponent`s net. The mechanism of prolonged DML in the axillary nerve may both tract and compress as the axillary nerve stretches across the humerus during movement. From this study it emerged that using the biceps and coracobrachialis muscles can create notable muscle compartment pressure on the musculocutaneus nerve. The significant differences detected in the neurophysiologic study of the musculocutaneous nerve between the ice hockey players and controls may reflect the fact that the forces acting on the shoulder and the elbow during ice hockey matches can effectively influence DML. Conclusion. The authors suggest two plausible causes for prolonged radial nerve DML: direct compression by the hypertrophied triceps muscle and stretching of the arm. The study suggests it is likely that a combination of skeletal muscle hypertrophy and excessive biomechanical demands on neurological structures during ice hockey matches may be a major etiologic factor in compression of the axillary, musculocutaneous and radial nerves.